Comparison of E-Commerce in UMKM Ledre Bojonegoro Regency with Analytical Hierarchy Process - Alfika, Mahaneny Dian; Moehadi, Moehadi; Susilo, Joko Hadi (MediaTrend, 2023)
Micro, Small, And Medium Enterprises (MSMEs) are crucial drivers of regional and national economic growth. The growth of MSMEs, coupled with increased employment opportunities and output, underscores their important role in economic development. The pace of technological advancement has created various e-commerce options. MSMEs must adapt to the demands of Industry 4.0 to ensure their longevity.  This study compares e-commerce options for marketing use by Ledre's Micro, Small, and Medium Enterprises in Bojonegoro Regency. The aim is to determine which platform is best using the Analytical Hierarchy Process method for effective decision support. Subjective evaluations are avoided, and technical terms are explained. The text adheres to conventional academic structure, provides logical progression, and uses formal language with precise vocabulary. The Analytical Hierarchy Process selects and identifies top-priority criteria and significant alternatives for each category of criteria in e-commerce. The categories include aspects of the promotion system, payment system, web design, and risk in Micro, Small, and Medium Enterprises (MSMEs) of Bojonegoro Regency. The Analytical Hierarchy Process prioritizes key-person quality over respondent quantity in research. According to the process calculation, the most crucial factor is risk, with a weight of 49.54%. Criteria for electronic marketing in Micro, Small, and Medium Enterprises should include optimizing social media, pay-at-site payment systems, easy-to-use website design, and legal protection risks. The primary option for Bojonegoro Regency Ledre Micro, Small, and Medium Enterprises to enhance sales through electronic marketing is the utilization of Shopee, an e-commerce platform.